2019
DOI: 10.1101/720037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Arabidopsis leucine-rich repeat receptor kinase MIK2 is a crucial component of pattern-triggered immunity responses to Fusarium fungi

Abstract: 8Fusarium is a genus of fungi causing severe economic damage in many crop species exemplified 9by Fusarium Head Blight of wheat or Panama Disease of banana. Plants sense immunogenic patterns 10 (termed elicitors) at the cell surface contributing to disease resistance via the activation of pattern-11 triggered immunity (PTI). Knowledge of such elicitors or corresponding plant immunity components is 12 largely lacking for Fusarium species. We describe a new peptide elicitor fraction present in several 13 Fusariu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Thus, Fusarium SCOOPLs trigger similar responses with Arabidopsis SCOOPs in a MIK2-dependent manner. This is consistent with the observation that the mik2 mutants were insensitive to the elicitor from different Fusarium spp 30. .…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, Fusarium SCOOPLs trigger similar responses with Arabidopsis SCOOPs in a MIK2-dependent manner. This is consistent with the observation that the mik2 mutants were insensitive to the elicitor from different Fusarium spp 30. .…”
supporting
confidence: 92%
“…In addition, MIK2 plays a role in response to diverse environmental stresses, including cell wall integrity sensing, salt stress tolerance, and resistance to the soil-borne fungal pathogen Fusarium oxysporum [26][27][28][29] . A recent study suggested that MIK2 functions as a PRR perceiving an unknown peptide elicitor from F. oxysporum to activate plant immunity 30 . Here, we provide genetic and biochemical evidence that MIK2 is the bona fide receptor of SCOOP family peptides.…”
Section: Introductionmentioning
confidence: 99%
“…MAMP recognition is mediated by pattern recognition receptors (PRRs) located at the cell surface (Macho and Zipfel, 2014) such as the CERK1 chitin receptor of Arabidopsis (Miya et al, 2007). Forward genetics in Arabidopsis identified the receptor-like kinase MIK2 as a potential PRR and as a crucial component to recognize and respond to MAMPs from Fo (Coleman et al, 2019). PRRs are mainly expressed in root zones vulnerable to pathogen entry resulting in a heterogenic and tissue-specific responsiveness to different MAMPs (Chuberre et al, 2018).…”
Section: The Timing and Amplitude Of Root Responses Upon Colonizationmentioning
confidence: 99%
“…PRRs are mainly expressed in root zones vulnerable to pathogen entry resulting in a heterogenic and tissue-specific responsiveness to different MAMPs (Chuberre et al, 2018). Responsiveness to chitin, for instance, is mostly confined to the mature zone and other parts of the root system are relatively insensitive to this MAMP and do not mount immune responses upon exposure to chitin (Millet et al, 2010;Coleman et al, 2019). This heterogeneity could explain why Fol typically does not penetrate mature root zones (Mes et al, 2000).…”
Section: The Timing and Amplitude Of Root Responses Upon Colonizationmentioning
confidence: 99%
“…The sub-1, qky-8 (all in Ler), and the sub-9 and qky-11 mutants (Col) have been characterized previously [44,47,50,51]. The prc1-1 [27], the1-1 [38], the1-6 [74], mik2-1 [39], mik2-3 [75], and ixr2-1 [30] alleles were also described previously. The sub-21 (Col) allele was generated using a CRISPR/Cas9 system in which the egg cell-specific promoter pEC1.2 controls Cas9 expression [76].…”
Section: Plant Work Plant Genetics and Plant Transformationmentioning
confidence: 99%